English, Identity, and the Digital Face of Higher Education: A Case Study of Saudi University Websites in Global Context - Sabir, Mona (Forum for Linguistic Studies, 2025)
In increasingly globalized academic contexts, English plays a central role in how non-Anglophone universities project their institutional identity. This study investigates how six Saudi universities use English on their official websites to construct institutional identity in a global context. Drawing on critical discourse analysis, linguistic landscape theory, and multimodal semiotics, the research analyzes bilingual digital content (such as mission statements, internationalization narratives, homepage structures, and visual layout) to explore the semiotic hierarchies shaping identity construction. The findings reveal a discursive bifurcation: English predominates in internationally oriented content, including research, partnerships, and rankings, while Arabic asserts national culture, religious values, and civic responsibility. Institutions with STEM specializations or private governance structures tend to foreground English more prominently, whereas religiously affiliated or regionally grounded universities maintain Arabic dominance. Across the sample, visual and structural cues reinforce English as a marker of academic modernity and global aspiration, often shaping the user's first impression of institutional identity. Rather than articulating a balanced bilingual identity, these websites reflect a strategic linguistic negotiation shaped by ideology, audience, and institutional ambition. The study contributes to debates on Englishization, institutional branding, and the politics of language in digital higher education, with particular relevance to contexts across the Global South where institutions seek to balance global competitiveness with cultural and linguistic rootedness.